2013
DOI: 10.1111/gwat.12061
|View full text |Cite
|
Sign up to set email alerts
|

Use of Machine Learning Methods to Reduce Predictive Error of Groundwater Models

Abstract: Quantitative analyses of groundwater flow and transport typically rely on a physically-based model, which is inherently subject to error. Errors in model structure, parameter and data lead to both random and systematic error even in the output of a calibrated model. We develop complementary data-driven models (DDMs) to reduce the predictive error of physically-based groundwater models. Two machine learning techniques, the instance-based weighting and support vector regression, are used to build the DDMs. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 46 publications
(57 reference statements)
0
53
0
2
Order By: Relevance
“…Recently, data-driven models such as artificial neural networks (ANN), support vector machines (SVM), adaptive neuro-fuzzy inference systems (ANFIS) and genetic programming (GP), and time series methods such as autoregressive moving average (ARMA) and autoregressive integrated moving average (ARIMA) have been proved efficient in forecasting hydrologic time series (e.g., groundwater level, water demand and inflow) [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Yoon et al [5] developed ANN and SVM models to forecast groundwater level fluctuations in a coastal aquifer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, data-driven models such as artificial neural networks (ANN), support vector machines (SVM), adaptive neuro-fuzzy inference systems (ANFIS) and genetic programming (GP), and time series methods such as autoregressive moving average (ARMA) and autoregressive integrated moving average (ARIMA) have been proved efficient in forecasting hydrologic time series (e.g., groundwater level, water demand and inflow) [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Yoon et al [5] developed ANN and SVM models to forecast groundwater level fluctuations in a coastal aquifer.…”
Section: Introductionmentioning
confidence: 99%
“…The ARIMA model was proved have better predictive ability compared to the ARMA model. Xu et al [14] built the instance-based weighting and support vector regression data-driven models to reduce the predictive error of groundwater models. The results of two real-world case studies showed that data-driven models can be applied effectively to reduce the root mean square error of the groundwater models.…”
Section: Introductionmentioning
confidence: 99%
“…( k x is the input vector, k y is the corresponding output value), and the regression function of SVM can be expressed as: (10) where w is a weight vector, ϕ is a nonlinear transfer function that implements transformation the nonlinear to linear relationship of input to output vectors, and b is a bias. Vapnik introduced the …”
Section: Support Vector Machines (Svms)mentioning
confidence: 99%
“…Therefore, data-driven models are a good choice when data are limited and the groundwater system is very complex [22]. Data-driven models such as multiple linear regression (MLR), Back-Propagation Artificial Neural Network (BP-ANN), Support Vector Machines (SVM) and Power Function Models (PFM), are gradually used for groundwater level prediction, and thus, comparative studies on the above prediction techniques have been widely used and applied by some researchers [23][24][25].…”
Section: Introductionmentioning
confidence: 99%